Assessment of Hepatic Masses Using CT scan - Shivaraju C S (Asian Journal of Medical Research, 2019)
Background: The accurate and reliable determination of the nature of the liver mass is critical, not only to reassure individuals with benign lesions but also, and perhaps more importantly, to ensure that malignant lesions are diagnosed correctly. The present study was conducted to assess hepatic masses using CT scan. Subjects and Methods: 52 patients diagnosed with different hepatic masses of both genders. CT examination were performed in all patients on Siemens-Somatom Emotion 6 slice third generation spiral CT. Results: Out of 52 patients, males were 32 and females were 20. Hepatic masses were abscess in 12, cholangio carcinoma in 7, hemangiomas in 4, focal nodular hyperplasia in 3, hepatocellular carcinoma in 6, hydatid cysts in 4, metastasis in 2 and simple cysts in 14 cases. The difference was significant (P< 0.05). CT has the sensitivity of 100%, specificity of 97.2%, PPV of 97.0% and NPV of 100%. Conclusion: CT has high diagnostic value in detection of hepatic masses.